1988
DOI: 10.1104/pp.88.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Control of the Accumulation of mRNAs for Light- and Heat-Inducible Chloroplast Proteins in Pea (Pisum sativum L.)

Abstract: The levels of the mRNAs for light-inducible, nuclear-coded chloroplast proteins vary rhythmically in pea (Pisum sativum L.) plants either grown in a dark-light cycle or under constant light conditions. This has been observed for the early light-inducible protein, the light-harvesting chlorophyll a/b protein, and the small subunit of the ribulose-1,5-bisphosphate carboxylase. The mRNA levels are high in the morning, exhibit a minimum in the first half of the night, and increase again during the second half of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…Circadian expression has been described in many genes encoding products that function in photosynthetic light harvesting, such as CAB (Kay and Millar, 1993), or in photosynthetic carbon assimilation, such as RBCS (Spiller et al, 1987;Giuliano et al, 1988;Otto et al, 1988; and RCA (Martino-Catt and Ort, 1992;. Our data show that in mature plants CAT2 mRNA accumulation demonstrates robust circadian oscillations in continuous darkness and continuous light, persisting for at least 5 d in continuous light.…”
Section: Discussionmentioning
confidence: 51%
“…Circadian expression has been described in many genes encoding products that function in photosynthetic light harvesting, such as CAB (Kay and Millar, 1993), or in photosynthetic carbon assimilation, such as RBCS (Spiller et al, 1987;Giuliano et al, 1988;Otto et al, 1988; and RCA (Martino-Catt and Ort, 1992;. Our data show that in mature plants CAT2 mRNA accumulation demonstrates robust circadian oscillations in continuous darkness and continuous light, persisting for at least 5 d in continuous light.…”
Section: Discussionmentioning
confidence: 51%
“…Oscillations in the level of Elip transcripts have been already reported in other species (Otto et al, 1988;Po¨tter and Kloppstech, 1993) and attributed to the presence of a circadian control. This type of regulation is actually predictable, since the genomic sequence of both Elip genes contains circadian regulatory elements (the ''CAANNN-NATC'' and ''GATA'' motives) in the 5¢-upstream region, which are present and conserved in clock controlled Lhc genes (Piechulla et al, 1998).…”
Section: Discussionmentioning
confidence: 93%
“…However, since it was reported that in barley and pea the level of Elip transcript fluctuates diurnally (Otto et al, 1988, Po¨tter and Kloppstech, 1993, we included in the experiment the analysis of transcripts and proteins in leaves maintained in the growing chamber at a light intensity of 120 lE/ m 2 s (LL). Samples were collected from LL and HL plants at the same times.…”
Section: Effect Of Light and Temperature On Elips Transcription And Amentioning
confidence: 99%
“…In pea, under heat-shock conditions, the abundance of mRNA corresponding to some low molecular mass hsps was found to vary during the day, indicating a circadian control of their accumulation (20). Our own studies of a second hsp homolog, P. nil hsp83, show that its expression is induced by light (6).…”
Section: Identification Of the Transcription Initiationmentioning
confidence: 97%